The Translation Shifts Applied To The Translated Text I Belog Lost Something - Suastra, I Made; Barta, Francicus I Made; Mas Indrawati, Ni Luh Ketut (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana, 2016)
The objective of this study was to discover the shift occurring in the text analysis in the level of word and phrase. The analysis was limited to the shift in the level of noun or the noun phrase utilized in the Source Language which is translated into the Target Language.The data were collected from the Balinese story I BelogKelangan as the source text and its English translation I Belog Lost Something as the target text compiled by I Gusti Made Sutjaja (2010).The data were elaborated on the analysis by Qualitative method and presented in the form of words and sentences based on the application of shift theory Vinay-Darlbenet (in Venuti, 2000). The result of this study showed that there were two types of shift applied to the text. They are grammatical structure shift called Transposition and point of view shift known as Modulation. There were two types of shift grammatical structure; Unit Shift and Category Shift. The data were merely showing the low to high units of translation such as from word into phrase and from the phrase into clause. Meanwhile, the category shift the only occurred in different word class from noun to verb. The shifts in point of view resulted in Lexical Dense where the implicit lexical was transferred explicitly, in contrast the explicit item was transferred implicitly referred to Lexical Loose. In addition, there was also the stress on the role of character. Shift cannot be avoided in translation because it involves two different languages which are different in linguistically and culturally. This research was expected to have contributions for future study on translation shift in Balinese text
Keywords: translation shift, transposition, modulation, noun/noun phrase